Cold sintering process assisted sintering for 8YSZ ceramic: A way of achieving high density and electrical conductivity at a reduced sintering temperature. (1st May 2023) - Lai, Qinyuan; Chen, Ju; Chang, Fan; Pei, Jingge; Liang, Yingyi; Chen, Xiyong; Feng, Qin; Cen, Zhenyong; Luo, Nengneng
Abstract: Yttria-stabilized zirconia (YSZ) is a well-studied and practically applied electrolyte for solid oxide fuel cells (SOFC), but the high sintering temperature causes some problems. In this work, 8 mol% yttria-stabilized zirconia (8YSZ) ceramics were prepared by a cold sintering process (CSP) technique associated with post-heat-treatment (PHT). The CSP was beneficial for getting high initial density for the green bulk, while the PHT could further improve the bulk density of the 8YSZ ceramics at a reduced sintering temperature. Electrochemical impedance spectra showed that the electrical conductivity was 0.060 S/cm at 850 °C for the 8YSZ ceramic prepared by CSP-PHT at 1300 °C, about twice of that prepared by CS. The improved electrical conductivity was attributed to the high density and the reduced activation energy relevant to refined grain size and increased bulk density. Our study demonstrates that the CSP-PHT is a promising technique for preparation of high-dense YSZ ceramics with improved electrical conductivity at a reduced sintering temperature.